(untitled) (Journal of the College of Basic Education, 2024)
The research was interested in focusing on how to find techniques that enable the designer to employ electronic lighting in the design of smart furniture, and to demonstrate the functional and aesthetic role. Lighting technology using optical fibers and solar panels and the use of LED technology in lighting in smart furniture allowed the designer the flexibility to achieve what ordinary lighting could not achieve. By controlling the way it is formed and the lighting colors used in the designs, and through the use of sensor technology in the design of smart furniture, it has become possible for a piece of smart furniture to respond to the mood and feelings of the user and the surrounding environment, which achieves economic, environmental and social benefits, opening wide scope for the designer to be creative in electronic lighting designs in Smart furniture is new and innovative. The research included a theoretical framework that included three topics, which we will discuss in turn.